Clinical outcomes of patients with advanced hepatocellular carcinoma treated with sorafenib: a retrospective study of routine clinical practice in multi-institutions - Lee, Sae Hwan (BMC Cancer, 2015)
BACKGROUND: Sorafenib is an orally administered multikinase inhibitor with antiangiogenic and antiproliferative properties. The results of large clinical trials demonstrate that sorafenib prolongs survival and the time to progression of patients with advanced hepatocellular carcinoma (HCC). The aim of the present study was to determine the outcomes of such patients who were routinely treated with sorafenib at multi-institutions in Korea, in contrast to formal clinical trials. METHODS: Between August 2007 and March 2012, patients with advanced HCC in seven referral medical centers in Daejeon-Chungcheong Province of Korea were retrospectively enrolled to evaluate treatment response, survival, and tolerability following administration of sorafenib. The treatment response was assessed in accordance with the Response Evaluation Criteria in Solid Tumor 1.1 guidelines. RESULTS: Among 116 patients, 66 (57%) had undergone treatment for HCC, and 77 (66%) were accompanied with Child-Pugh A cirrhosis. The median duration of sorafenib treatment was 67 days (range 14–452 days). Median overall survival and median time to progression were 141 days and 90 days, respectively. Complete response, partial response, and stable disease were achieved for 0%, 2%, and 29% of patients, respectively. Overall median survival, but not the median time to progression, was significantly shorter for patients with Child-Pugh B cirrhosis compared with those with Child-Pugh A cirrhosis (64 days vs 168 days, P = 0.004). Child-Pugh B cirrhosis (P = 0.024) and a high level of serum alpha-fetoprotein (P = 0.039) were independent risk factors for poor overall survival. Thirty-nine (34%) patients experienced grade 3/4 adverse events such as hand-foot skin reactions and diarrhea that required dose adjustment. CONCLUSIONS: The clinical outcomes of sorafenib-treated patients with advanced HCC were comparable to those reported by formal clinical trial conducted in the Asia-Pacific region. Underlying hepatic dysfunction was the most important risk factor for shorter survival.